Difference and structure: deleuze and ontic structural realism - Webster, G (2022)
A branch of the interpretative literature on the work of the philosopher Gilles Deleuze is more or less dedicated to emphasizing his engagements with mathematics and the sciences and to presenting his thought to an audience of philosophers of science working in the analytic tradition. Such scholarship, however, generally fails to connect Deleuze to the ideas and problems that motivate contemporary philosophers of science. Still, an emerging interest in Deleuze is observable within the philosophy of science literature. This thesis aims to encourage and cultivate this interest by presenting a direct, comparative study of Deleuze’s philosophy of difference in relation to ontic structural realism. I claim that identifying and examining the various affinities (and differences) between these two positions, which I take to be a worthwhile task in and of itself (i), allows us: (ii) to force Deleuze’s philosophical position into greater exegetical clarity, (iii) to critically reappraise (and reject) the way in which numerous commentators understand the role of science within Deleuze’s philosophical writings, and (iv) to propose some interesting challenges and adjustments to the ontic structural realist view.